Identification of striated muscle activator of Rho signaling (STARS) as a novel calmodulin target by a newly developed genome-wide screen. Issue 1 (July 2016) - Furuya, Yusui; Denda, Miwako; Sakane, Kyohei; Ogusu, Tomoko; Takahashi, Sumio; Magari, Masaki; Kanayama, Naoki; Morishita, Ryo; Tokumitsu, Hiroshi
Graphical abstract: Highlights: Genome-wide CaM interaction screening method is newly developed. Striated muscle activator of Rho signaling is identified as a novel CaM target. Ca 2+ /CaM interacts with STARS through its 1–14CaM binding motif. Regulation of STARS-mediated transcriptional activation by Ca 2+ /CaM is proposed. Abstract: To search for novel target(s) of the Ca 2+ -signaling transducer, calmodulin (CaM), we performed a newly developed genome-wide CaM interaction screening of 19, 676 GST-fused proteins expressed in human. We identified striated muscle activator of Rho signaling (STARS) as a novel CaM target and characterized its CaM binding ability and found that the Ca 2+ /CaM complex interacted stoichiometrically with the N-terminal region (Ala13–Gln35) of STARS in vitro as well as in living cells. Mutagenesis studies identified Ile20 and Trp33 as the essential hydrophobic residues in CaM anchoring. Furthermore, the CaM binding deficient mutant (Ile20Ala, Trp33Ala) of STARS further enhanced its stimulatory effect on SRF-dependent transcriptional activation. These results suggest a connection between Ca 2+ -signaling via excitation-contraction coupling and the regulation of STARS-mediated gene expression in muscles.